General practice perspective on the use of telehealth during the COVID-19 pandemic in Australia using an Action Research approach: a qualitative study. Issue 10 (27th October 2022) - Hardie, Rae-Anne; Thomas, Judith; Li, Julie; Pearce, Christopher; Georgiou, A
Abstract : Objectives: Telehealth has emerged as a viable and safe mode of care delivery in Australia during the COVID-19 pandemic. However, electronic general practice data reveal differences in uptake and consultation mode, which we hypothesise may be due to potential barriers impacting on quality of care. We aimed to identify the benefits and barriers of telehealth use in general practice, using an 'Action Research' approach involving general practitioners (GPs) and general practice stakeholders. Design: Qualitative focus group performed within a broader Action Research methodology. Setting: A focus group was held in August 2021, with general practice participants from Victoria, Australia. Participants: The study consisted of a purposive sample of 11 participants, including GPs (n=4), representatives from three primary health networks (n=4) and data custodian representatives (n=3) who were part of a project stakeholder group guided by an Action Research approach. Methods: Semistructured interview questions were used to guide focus group discussions via videoconference, which were recorded and transcribed verbatim for analysis. The transcript was analysed using an inductive thematic approach. Results: Emerging themes included evolution of telehealth, barriers to telehealth (privacy, eligibility, technology, quality of care, sociodemographic and residential aged care barriers) and benefits of telehealth (practice, quality of care, sociodemographic and residential aged care benefits). Conclusion: The findings highlight a range of barriers to telehealth that impact general practice, but also provide justification for the continuation and development of telehealth. These results provide important context to support data-driven population-based findings on telehealth uptake. They also highlight areas of quality improvement for the enhancement of telehealth as a valuable tool for routine general practice patient care.